A carne se fez verbo: confissão cristã e sexualidade em Michel Foucault - Calçado, Thiago (2015)
This thesis deals with the Christian confession and its relation to the constitution of sexuality, from the Michel Foucault approach. Analyzing the courses offered by the French philosopher in the early 80s, Du gouvernement des vivants; Mal faire, dire vrai; Subjectivité et vérité presents here the subjective process found in confession mechanisms and self-examination in primitive Christianity. The disciplinary procedures of discursive production, according to what we try to show here, are a verbalization of their own interiority, fundamental to the formation of the subject of desire. More than that, to establish the relationship between the sexual morality from the early centuries of our era and the emergence of Christian flesh. The aim is also to point out how the meat became verb and at the same time, the set of disciplinary and institutional practices, showing how it relates to the theme of the pastorate and power, from the perspective of moral displacement from ethics to desire. In this sense, it is expected to corroborate Foucault studies from the perspective of a critical history of thought, based on sexuality and its relationship to the truth